Developmental trajectory of interpersonal motor alignment: Positive social effects and link to social cognition. (November 2020) - Rauchbauer, Birgit; Grosbras, Marie-Hélène
Highlights: Interpersonal motor alignment (IMA) has positive effects on healthy social life. IMA - mimicry, synchrony, automatic imitation - is studied throughout development. It relies on motor resonance brain mechanisms identified throughout development. It is modulated by contextual and personal factors. IMA is underinvestigated in adolescence, yet it may aid to enhance resilience. Abstract: Interpersonal motor alignment is a ubiquitous behavior in daily social life. It is a building block for higher social cognition, including empathy and mentalizing and promotes positive social effects. It can be observed as mimicry, synchrony and automatic imitation, to name a few. These phenomena rely on motor resonance processes, i.e., a direct link between the perception of an action and its execution. While a considerable literature debates its underlying mechanisms and measurement methods, the question of how motor alignment comes about and changes in ontogeny all the way until adulthood, is rarely discussed specifically. In this review we will focus on the link between interpersonal motor alignment, positive social effects and social cognition in infants, children, and adolescents, demonstrating that this link is present early on in development. Yet, in reviewing the existing literature pertaining to social psychology and developmental social cognitive neuroscience, we identify a knowledge gap regarding the healthy developmental changes in interpersonal motor alignment especially in adolescence.